Diagnosis for H-Pylori by Various Staining Methods in Gastric Biopsy Specimens - Raees Abbas Lail, Qurrat-ul-Ain Tahir, Sadaf Shafique, Saira Siraj, Sajjad Hussain Sabir, Nadia Naseem, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To run a comparison between specificity, sensitivity, PPV (positive predictive value) (PPV) & NPV (negative predictive value) of the three varied H. pylori detection methods used in the study. Materials and Methods: It is a retrospective descriptive study that was carried out at Histopathology wing of Pathology Department, Sahiwal Medical College, Sahiwal. It comprised of entire cases of gastritis which were histopathologically proven by using Hematoxylin and Eosin, Giemsa and Immunohistochemical stains on biopsies taken by endoscopy and were sent from Gastroenterology Department Govt. Haji Abdul Qayyum Teaching Hospital, Sahiwal from January 2020 to the month of December 2020. SPSS version 20 was employed to evaluate all the received data. Results: Amongst 95 samples, IHC (Immunohistochemistry) was ranked highest, displaying 100% specificity, 100% positive predictive value and 94.74% sensitivity. The H&E stain followed IHC, displaying 100% and 94.44% specificity and sensitivity respectively. The Giemsa stain was the runner up, displaying 95.65% specificity and 94.12% sensitivity. Conclusions: Histologically, H. pylori infection was associated more with chronic active gastritis as compared with chronic gastritis. The three dissimilar staining methods achieved sensitivity, specificity, positive predictive value and negative predictive values equally well. IHC is a precise method for detection of H.Pylori in gastric biopsies with high sensitivity and specificity. It is suggested to use more than one staining method where H.pylori level is low, it will minimize false-negative rate.